Personnel relationship management in RTE - Guo, Ying (Харківський національний автомобільно-дорожній університет, 2024)
In this qualification paper, theoretical provisions for managing the relationships between the RTE and its personnel have been improved. A new definition of the concept of "enterprise personnel relationship management" is proposed. A methodological approach for assessing the level of relationships between the RTE and its personnel has been refined. This approach is based on a two-dimensional matrix that evaluates the value of employees to the RTE and their loyalty to the enterprise. Strategies for internal marketing have been developed corresponding to the level of relationships between the RTE and its personnel. Predictive assumptions for the development of the research object - The proposed methodological and practical developments can be applied to enhance personnel management systems at other enterprises, especially in the transport sector.
Keywords: relationships; personnel; internal marketing; management; management system; interaction; assessment; loyalty